2021
DOI: 10.1186/s12894-021-00873-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of angioembolization in the management of blunt renal injuries: a systematic review

Abstract: Background Recently, renal angioembolization (RAE) has gained an important role in the non-operative management (NOM) of moderate to high-grade blunt renal injuries (BRI), but its use remains heterogeneous. The aim of this review is to examine the current literature on indications and outcomes of angioembolization in BRI. Methods We conducted a search of MEDLINE, EMBASE, SCOPUS and Web of Science Databases up to February 2021 in accordance with PRI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
1
1
0
6
Order By: Relevance
“…These results are consistent with those of a multicenter AAST study that showed that a nephrectomy was the most common intervention for bleeding in advanced trauma in 13% of cases, whereas angioembolization was performed in only 6% of patients [22]. Angioembolization of renal injuries is associated with a high success rate, even in patients with high-grade injuries [3,24]. In the present study, nonoperative management was performed in 98.5% of all patients, and was successful in 97.8% of patients with high-grade renal injuries.…”
Section: Discussionsupporting
confidence: 88%
“…These results are consistent with those of a multicenter AAST study that showed that a nephrectomy was the most common intervention for bleeding in advanced trauma in 13% of cases, whereas angioembolization was performed in only 6% of patients [22]. Angioembolization of renal injuries is associated with a high success rate, even in patients with high-grade injuries [3,24]. In the present study, nonoperative management was performed in 98.5% of all patients, and was successful in 97.8% of patients with high-grade renal injuries.…”
Section: Discussionsupporting
confidence: 88%
“…According to recent protocols, the initial management of renal trauma depends on hemodynamic status rather than the grade of the injury. For hemodynamically stable patients, conservative management, including expectant management or angioembolization, is recommended [5,6]. According to the European Association of Urology, the World Society of Emergency Surgery (WSES) and AAST, surgical management should be considered for hemodynamically unstable patients [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…El trauma renal corresponde a un 10% de todos los traumas abdominales; de ellos, un 90% comprende el trauma cerrado. Con respecto a las intervenciones asociadas, el manejo secuencial conservador o «paso a paso» ha logrado disminuir las tasas de nefrectomía innecesarias, ubicándose en un 28% en la actualidad 1,2 . Una de las herramientas disponibles en la actualidad como parte del tratamiento del paciente con trauma renal cerrado de alto grado es la angioembolización 2 .…”
unclassified
“…Con respecto a las intervenciones asociadas, el manejo secuencial conservador o «paso a paso» ha logrado disminuir las tasas de nefrectomía innecesarias, ubicándose en un 28% en la actualidad 1,2 . Una de las herramientas disponibles en la actualidad como parte del tratamiento del paciente con trauma renal cerrado de alto grado es la angioembolización 2 . Consecuentemente, vale la pena conocer cuáles son los factores predictores para realizar una intervención temprana con fines de detener el sangrado, las tasas de éxito de la primera o segunda angioembolización y los predictores de falla.…”
unclassified
See 1 more Smart Citation